An analysis of the utility of digital materials for high school students with intellectual disability and their effects on academic success - Deveci Topal, Arzu; Kolburan Geçer, Aynur; Çoban Budak, Esra (Universal access in the information society, 2023)
This study thoroughly examines the usability of digital materials, to establish a classroom environment in which technology is integrated into teaching practices using tablet computers and interactive smart boards. The study was conducted at a special education vocational school, where students with intellectual disability receive training. The integration of technology was made to the Natural Disasters unit (erosion, landslide, flood, earthquake, and digital story developed on the subject of flood) in the Social Science syllabus. This study also aims to develop multimedia applications and apply these to teaching activities, and additionally to increase the learning competencies of students in the subject of Social Sciences. This study involved eight students who have mild intellectual disability at a vocational high school. A thorough multiple probe design was used among single-subject research models. Comparison of the results revealed that students’ post-test scores increased significantly when compared to the pre-test scores, and that the teaching materials had a significantly positive impact on their learning process. Moreover, the effect of the prepared digitalized materials on learning was determined to be high in terms of its application in special education schools. Students indicated that they liked these activities which they engaged on computers, as well as the interactive multiple choices questions, and wished to have such creative applications made available for other subjects such as Turkish, Mathematics, Music, and Art.